Understanding forced adoption of self-service technology: the impacts of users' psychological reactance. Issue 8 (3rd August 2019) - Feng, Wenting; Tu, Rungting; Lu, Tim; Zhou, Zhimin
ABSTRACT: With the rapid development of artificial intelligence, information system, and mobile technologies, some companies (e.g. airlines) consider fully replacing service employees with self-service technologies (SSTs) to cut down costs and to increase efficiency. However, replacing full services with SSTs sometimes fail to deliver the benefits companies have hoped for: users may feel that they are being forced to use SSTs and show resistance to the new technologies. To investigate why users show resistance, we draw inferences from psychological reactance theory and argue that users may perceive the forced adoption as a threat, which leads to resistance of SSTs. A conceptual model was developed and an empirical study was conducted. The results show that, under a forced situation, users are likely to perceive the forced adoption as a threat to their freedom, causing them to have negative emotions and perceptions towards the SSTs, and, in turn, their adoption intention decreases and switch intention increases. The findings provide insights on why users show resistance to SSTs and highlight the impacts of the motivational state of psychological reactance.